Gerakan Koalisi Masyarakat Sipil Anti Kekerasan Seksual (KOMPAKS) dalam Mengawal Pengesahan Undang-Undang Tindak Pidana Kekerasan Seksual (UU-TPKS) - Puspitasari, Dia; Sadono, Teguh Priyo; Pramono, Bambang Sigit (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Gender-based social movements are often carried out by civil society for humanitarian purposes. Movement strategies are formulated in various ways, one of which is through political communication by civil society. The Civil Society Coalition Against Sexual Violence (KOMPAKS) is a civil society movement that supports the ratification of the Sexual Violence Crime Law (UU TPKS). KOMPAKS consists of various elements of civil society, namely individuals, academics, civil society organizations, etc. KOMPAKS actively carries out social movements with various strategies, one of which is using political communication. This study aims to analyze the KOMPAKS Movement strategy in overseeing the TPKS Law using the Giddens Structuration perspective. The method used in this study is a case study of KOMPAKS in the context of social movements. However, this study has limitations because it only focuses on the KOMPAKS movement strategy. The results of this study indicate that the movement strategy carried out by KOMPAKS is gender-based, through political communication of various government stakeholders, education to both civil and political communities regarding the substance of the TPKS Law. The KOMPAKS Movement shows the dominance of agents rather than structures, namely the TPKS Law. Theoretically, there is no structuring process that occurs in the KOMPAKS movement, instead there is agent dominance over the structure. In the context of this research. the agent in question is KOMPAKS, while the structure is the TPKS Law, so theoretically this is what caused the ratification of the TPKS Law to take almost 10 years to be ratified.